Gas-sensing array application for on-line monitoring in a heat-responsive bioprocess of Streptomyces griseus HUT 6037 - Jung, Ho-Sup; Park, Kyung-Min; Kang, Do Hyun; Kwak, Moon Kyu; Lim, Seokwon; Chang, Pahn-Shick; Kim, Keesung (Food science and biotechnology, 2015)
The stress-responsive bioprocess concept has been developed into an environmentally friendly biosensor with low energy consumption and high recovery yield. To improve chitosanase production during Streptomyces griseus cultivation, heat-stress was applied to the bioprocess with monitoring using an on-line gas sensing system. When exposed to heat-stress with liposomes, the chitosanase productivity was 2.6 times greater than for conventional cultivation. The mixed gas components could be distinguished using a principal component analysis during chitosanase production. The online-monitoring system reflected basic changes in growth conditions and metabolite formation in cells. The array type gas-sensing system was capable of detecting bacterial infection faster than conventional sensor systems. The gas sensor system can play a key role in monitoring and controlling stress levels in a stress-responsive bioprocess.